2003
DOI: 10.1152/advan.00041.2002
|View full text |Cite
|
Sign up to set email alerts
|

Student Retention of Course Content Is Improved by Collaborative-Group Testing

Abstract: We recently reported that collaborative testing (i.e., group test taking) increased student performance on quizzes. It is unknown, however, whether collaborative testing improves student retention of course content. Therefore, this study was designed to test the hypotheses that collaborative-group testing improves student retention of course content. To test this hypothesis, our undergraduate exercise physiology class of 38 students was randomly divided into two groups: group A (n = 19) and group B (n = 19). D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

14
157
2
2

Year Published

2009
2009
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 171 publications
(175 citation statements)
references
References 8 publications
14
157
2
2
Order By: Relevance
“…It is anticipated that traditional exams place an emphasis on numeric aspects of learning, which fosters a fear of failure, increases anxiety, undercuts interest, reduces intrinsic motivation, heightens competitiveness, and depresses creativity. [6][7][8][9] The flipped exam model, however, addresses these limitations and offers an occasion to determine how well students perform when they are given an opportunity to collaborate with and learn from their peers while being provided with educational resources. Further, in a constructivist paradigm, the flipped exam allows students to actually focus on the 'process of learning' rather than the 'correct answer'.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is anticipated that traditional exams place an emphasis on numeric aspects of learning, which fosters a fear of failure, increases anxiety, undercuts interest, reduces intrinsic motivation, heightens competitiveness, and depresses creativity. [6][7][8][9] The flipped exam model, however, addresses these limitations and offers an occasion to determine how well students perform when they are given an opportunity to collaborate with and learn from their peers while being provided with educational resources. Further, in a constructivist paradigm, the flipped exam allows students to actually focus on the 'process of learning' rather than the 'correct answer'.…”
Section: Introductionmentioning
confidence: 99%
“…Further, in a constructivist paradigm, the flipped exam allows students to actually focus on the 'process of learning' rather than the 'correct answer'. [6][7][8][9][10] Educational intervention trials indicate that students performed better when the flipped exam model was utilized. For example, in a trial of this technique among Post-Baccalaureate students at Wayne State…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, in (Bloom, 2009) it was found that collaborative exam scores were also higher than the ones earned in individually taken exams during which students were allowed to use course textbooks and their notes. Further, some researchers show that students' performance also improved in a longer perspective, as indicated by post-tests taken some time after the collaborative exam (Cortright et al, 2003;Jensen et al, 2002;Simpkin, 2005). Notice that in our research we established a positive and statistically significant impact of participation in the tournament on students' achievements in the post-test.…”
Section: Academic Benefitsmentioning
confidence: 99%
“…Nowadays, we can find different proposals of combining these two types of assessments (Fakcharoenpohl & Stelzer, 2014;Pawl et al, 2013;Yu & Li, 2014), and the boundaries between them become more and more vague. One example of such an approach is "collaborative testing" -an idea of giving students the opportunity for working in groups during an exam (Guest & Murphy, 2000), at the end of an individual exam (Lusk & Conklin, 2003) or, more often, after the first, but before the second exam taken individually (Cortright et al, 2003;Ives, 2014;Rao et al, 2002) (the last two are sometimes named "two-stage exams"). Research has shown that there are many benefits of utilizing collaborative testing as a constructivist learning method.…”
Section: Introductionmentioning
confidence: 99%
“…pyramid exams), where students first take an exam individually and then take the same exam together with their peer groups. Each exam is then weighted as a combination of students' individual and group scores [11,21,24,25]. However, we were concerned that under-performers and under-engaged students would slip through the cracks by using the follow-up group exam as a crutch.…”
Section: Introductionmentioning
confidence: 99%